Des Expressions Langagières Aux Re Présentations Identitaires Approche Sociolinguistique Des Affiches Publicitaires De Gastronomie En Milieu Urbain Algérien - Khattab, Nadji (جامعة محمد بوضياف المسيلة - كلية الآداب واللغات, 2016)
We tried hard, in this article, to report the Algerian advertising discourse from the perspective of urban sociolinguistics. We are part of a corpus made up of posters referring to eating and drinking, all documented in the town of Setif (Algeria) to answer the following question: How to manifest the "dynamicity" identity in the poster local gastronomy advertising? Thus, such a question prompted us to choose the urban sociolinguistics as a theoretical framework for analysis and to reveal the nature that exists between language and identity through advertising poster.
حاولنا من خلال هذا المقال إبراز تحليل للخطاب الإشهاري الجزائري، من منظور علم الاجتماع اللغوي الحضري. كانت انطلاقتنا من مدونة مكونة من عدد هام من الملصقات الإشهارية للأكل والشرب، كلها مستلة من مدينة سطيف (الجزائر)، وهذا محاولة منا للإجابة عن الإشكالية التالية: كيف تظهر (أو بما تتميز) حركية الهوية من خلال الملصقات الإشهارية للطهي؟ دفعنا هذا التساؤل إلى اختيار علم الاجتماع اللغوي كإطار ومنهج تحليلي، وهذا بهدف الكشف عن العلاقة بين اللغة والهوية من خلال الملصقة الاشهارية.
Keywords: وسائل الإعلام -- وسائل الإتصالات -- الخطاب الإشهاري -- الجزائر -- المجتمع الجزائري -- التسويق والترويج -- علم الإجتماع اللغوي -- مستخلصات الأبحاث